The post-industrial landscape: pretty after ugly - Ismail, Nor Atiah; Maulan, Suhardi; Mohd Shariff, Mustafa Kamal; Daud, Marina; Mazlan, Maizura; Haddadian, Maryam (Universiti Putra Malaysia Press, 2014)
As cities grow and compete to become more sustainable, their action is often to rectify mistakes of their unsustainable past. Remnants of industrial activity, brownfield sites provide opportunity where cities can undo the past and reinvent a greener future.